The influence of occupational stress towards employees’ job satisfaction and job performance (a case of Grand Blue Wave Hotel Shah Alam) / Amirah Che Ayub - Che Ayub, Amirah (2013)
Employees in hotel industries are believed to face high level of occupational stress which leads to higher percentage of turnover.Operational employees may experience high level of stress as a result of the conflicting demands of the company, supervisors, and customers. Besides, employees in the operational line are considered the main interactive contact points which fulfill customers demand on board. The main objective of this paper is to analyze the influence of occupational stress towards employee job performance, as well as the effect of job satisfaction as mediator between the variables among operation staff at Grand Blue Wave hotel Shah Alam. Six sources of occupational stress highlighted in this study areintrinsic factor, organization roles, work relationships, career development issues, organizational factors and home-work interface. This study uses a self-administered questionnaire with 35 items used to measure the variables in the study context. According to the results of this study, employees who are under stress in terms of career development and home-work interface may not necessarily have lower job satisfaction and performance. Furthermore, this study also found that intrinsic factor, organization roles, work relationships and organizational factors in occupational stress do not have significant influence towards job performance. However, analysis had shown that occupational stress does mediate the employee job performance at the studied hotel. This may happen as a result of sufficient and effective management practices which are concern on regulating the level of stress among employees.